Critique and Content Analysis of Exegetical Methods of Quran - Khadije Hosseinzade; Seyyed Ahmad Bardei; Reza Habibi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
A proper textbook has special features and criteria which make it distinguished from other books. Since textbooks have determining and key roles in the learning process, content analysis of textbooks has prominent significance. So, this article aims to clarify how much “Exegetical Methods of Quran” is adaptive with features and criteria of textbooks? The mothed is used here is descriptive-analytic, relying upon content analysis techniques. Studying the book and comparing it with criteria of textbooks show that this book is totally adapted with criteria of novelty and perfection content. However, from the perspective of content criteria of textbooks, %67 of goals, %65 of exercises, %50of pre-advance-organizers and %10/63 of summaries are not in the suitable condition.